PEDUM PAMONG AGAINST TEGAK UMAH TUA IN BALINESE CUSTOMARY LAW - Sari, Kadek Dwinta Pradnya; Resen, Dr. Made Gde Subha Karma (jfpublisher, 2024)
Umah Tua land is essential for the Balinese community's balance and must be preserved by every generation. Balinese customary law includes the concept of pedum pamong, which involves temporarily distributing inherited property until a final distribution occurs. However, there are no specific regulations in Balinese law addressing pedum pamong and its legal consequences for Umah Tua. This is neccessary as Umah Tua ownership is communal and includes preservation duties, especially for the tegak sanggah within Umah Tua. This article aims to explain the concept of pedum pamong in the context of Balinese customary law and analyze its juridical consequences on the tegak umah tua. This research applies a descriptive normative legal approach, reliant on the analysis of literature related to Balinese customary law. The research findings revealed that no specific regulation on pedum pamong is identified in Balinese customary law. Pedum pamong focuses on the temporary distribution of inheritance until it is distributed in perpetuity. Due to its temporary nature, the ownership of tegak umah objects within the scope of umah tua may change upon the testator's passing or cremation, with the exception of tegak bale dangin and merajan. Therefore, it is necessary to establish a specific and comprehensive guideline regarding pedum pamong in Balinese customary law.